Myocardial perfusion scintigraphy for risk stratification of patients with coronary artery disease: the AMICO registry. (8th February 2021) - Pugliese, NR; Buechel, R; Coceani, M; Clemente, A; Kaufmann, PA; Marzullo, P; Gimelli, A
Abstract: Funding Acknowledgements: Type of funding sources: None. onbehalf: AMICO registry Background. Clinical evidence promotes therapy titration based on patient risk stratification in coronary artery disease (CAD). Purpose. We assessed the prognostic value of myocardial perfusion scintigraphy (MPS) with cadmium-zinc-telluride in addition to clinical and coronary anatomy analysis. Methods and Results. We prospectively enrolled 1464 patients (26% females, 69.5 ± 10.4 years) referred for stress-rest MPS. All the patients underwent invasive coronary angiography (1171, 80%) or coronary computed tomography angiography (293, 20%). We defined a composite endpoint of cardiovascular death and non-fatal MI. After a median follow-up of 3.5 years (interquartile range 2 – 6 years), we observed 127 events (Table). Summed stress score (SSS) had the highest accuracy in predicting primary endpoint with a ROC-derived cut-off of SSS > 8 (>10% myocardium). SSS > 8 portended the lowest survival probability at Kaplan–Meier analysis (p < 0.0001; Figure A). The Cox-regression analysis indicated SSS as an independent predictor of the composite endpoint, along with fasting blood glucose and total cholesterol and contrary to coronary anatomy parameters. Patients with SSS > 8 treated with optimal medical therapy (OMT) had the largest area of necrosis, the lower ischemic burden, the most compromised LV systo-diastolic function and the highest LV mass, but received a less aggressive treatment in comparison to early revascularized patients. Survival analysis revealed patients with SSS ≤ 8 had the greater freedom from events, irrespective of the treatment strategy, while the group with SSS > 8 and OMT had the worst outcome, followed by patients with SSS > 8 and early revascolarization (log-rank test: all p < 0.0001). Plotting the estimates from proportional-hazard modelling against SSS (reference level: SSS = 4) shows a risk curve for the primary endpoint that increase for SSS > 4 and reach a plateau for values >12 (Figure B). Conclusion. The extension of stress perfusion abnormalities constitutes a robust independent predictor of future adverse events after adjustment for multiple clinical parameters and coronary anatomy analysis. MPS could help refine risk stratification of patients with known or suspected CAD.